MYOCARDIAL INFARCTION AS TYPICAL PRESENTATION OF NONCOMPACTION CARDIOMYOPATHY - O. V. Blagova (Российский кардиологический журнал, 2016)
The main clinical presentation of noncompaction myocardium (NCM) as nosologic unit are thromboembolic syndrome, heart failure, mostly ventricular arrhythmias and ischemia itself, related to insufficient myocardium blood supply under the noncompacted layer. Also, there are only sporadic cases of myocardial infarction described (MI), including “idiopathic”, in NCM.Aim. To check the prevalence of acute MI in patients with NCM, the specialties of clinical picture, diagnostics, and its probable specific mechanisms, influence on prognosis and its ways of prevention.Material and methods. Totally, 10 patients included, 7 males and 3 females, mean age — 46,3±15,8 y. o., (30 to 76 y. o.) among 85 patients with verified NCM diagnosis, set in accordance with harmonized visual criteria, and developed MI on this background. In 4 cases the NCM is confirmed with three visualizing criteria (EchoCG, MSCT, MRI of the heart), in 4 other — with the two. Mean follow-up was 10,5 [1,75; 32,25] months — from 1 month to 1 year. All patients underwent ECG, ambulatory ECG recording by Holter, EchoCG, assessment of antibodies against various heart antigens, PCR for DNA of parvovirus and B19, as well as herpes group, in blood; 7 coronary arteriographies, 7 MSCT of the heart, measurement of Troponin (n=7), morphological investigation of the heart with PCR-diagnostic of viral infection (n=6), MRI (n=5) and myocardium scintigraphy with 99mТс (n=6).Results. In 4 among 10 patients the development of MI was the first presentation of NCM. Prevalence of coronary atherosclerosis in those with MI and NCM was 20%, however in most cases development of MI was not related with coronary atherosclerosis. Intracardiac thrombosis was verified in 60% of patients with MI, embolism to other organs in 30%. The following mechanisms of MI established: 1) thromboembolism to coronary arteries if thrombi are present in the left chambers of the heart (atrium a. w.a. ventricle), verified in 1 patient at autopsy, and is suspected in other five; 2) concomitance of myocarditis, incl. viral, with microvasculitis development and thrombosis of intramyocardial arteries and focal necrosis in ischemized myocardium (n=6); 3) thrombosis of coronary arteries with presence of hemodynamically significant atherosclerosis (probably 1 patient); 4) sudden worsening of blood supply under noncompacted layer under the circumstances of low cardiac output by secondary origins.Conclusion. MI is typical and unrare complication of NCM: its prevalence reached 11,8% in separate registry of 85 patients with NCM syndrome. Four probable mechanisms of MI (necrosis) in NCM (embolism, thrombosis, myocarditis, microcirculation disorder) might be comorbid. The development of MI leads to serious worsening of the baseline systolic dysfunction and ventricular rhythm disorders: mortality among MI patients with NCM is 20% with the mean time of follow-up 10,5 months. As a preventive matter against MI in NCM should be concerned the anticoagulants at least for atrial fibrillation and in systolic dysfunction, on-time diagnostics and myocarditis management.